Back where it belongs: 11β-hydroxyandrostenedione compels the re-assessment of C11-oxy androgens in steroidogenesis. (5th April 2021) - Barnard, Lise; du Toit, Therina; Swart, Amanda C.
Abstract: Adrenal steroidogenesis has, for decades, been depicted as three biosynthesis pathways –the mineralocorticoid, glucocorticoid and androgen pathways with aldosterone, cortisol and androstenedione as the respective end products. 11β-hydroxyandrostenedione was not included as an adrenal steroid despite the adrenal output of this steroid being twice that of androstenedione. While it is the end of the line for aldosterone and cortisol, as it is in these forms that they exhibit their most potent receptor activities prior to inactivation and conjugation, 11β-hydroxyandrostenedione is another matter entirely. The steroid, which is weakly androgenic, has its own designated pathway yielding 11-ketoandrostenedione, 11β-hydroxytestosterone and the potent androgens, 11-ketotestosterone and 11-ketodihydrotestosterone, primarily in the periphery. Over the last decade, these C11-oxy C19 steroids have once again come to the fore with the rising number of studies contradicting the generally accepted notion that testosterone and it's 5α-reduced product, dihydrotestosterone, are the principal potent androgens in humans. These C11-oxy androgens have been shown to contribute to the androgen milieu in adrenal disorders associated with androgen excess and in androgen dependant disease progression. In this review, we will highlight these overlooked C11-oxy C19 steroids as well as the C11-oxy C21 steroids and their contribution to congenital adrenal hyperplasia, polycystic ovarian syndrome and prostate cancer. The focus is on new findings over the past decade which are slowly but surely reshaping our current outlook on human sex steroid biology. Graphical abstract: Image 1